2019
DOI: 10.1186/s12940-019-0549-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term association between ambient temperature and homicide in South Africa: a case-crossover study

Abstract: BackgroundCriminology research has traditionally investigated sociodemographic predictors of crime, such as sex, race, age, and socioeconomic status. However, evidence suggests that short-term fluctuations in crime often vary more than long-term trends, which sociodemographic factors cannot explain. This has redirected researchers to explore how environmental factors, such as meteorological variables, influence criminal behavior. In this study we investigate the association between daily ambient temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
1
10
1
Order By: Relevance
“…In this study, a majority of participants reported one or more physical symptoms of heat exposure, and close to three of every four residents reported mental health symptoms during a heat wave, largely due to uncertainty, confinement, and a sense of desperation. These findings are consistent with studies linking heat waves to increased respiratory and cardiovascular morbidity and mortality as well as suicidal and homicidal behavior [ 20 , 21 , 22 , 23 , 24 , 25 ] and increased monthly temperatures of 30C and higher to greater mental health difficulties [ 16 ]. However, only two of the participants sought medical attention for these problems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, a majority of participants reported one or more physical symptoms of heat exposure, and close to three of every four residents reported mental health symptoms during a heat wave, largely due to uncertainty, confinement, and a sense of desperation. These findings are consistent with studies linking heat waves to increased respiratory and cardiovascular morbidity and mortality as well as suicidal and homicidal behavior [ 20 , 21 , 22 , 23 , 24 , 25 ] and increased monthly temperatures of 30C and higher to greater mental health difficulties [ 16 ]. However, only two of the participants sought medical attention for these problems.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, low-income residents of urban heat islands are more susceptible to heat-related morbidity and mortality due to increased temperatures, lack of tree cover and green space, low socioeconomic status, lack of material resources, and low saturation of air conditioning (AC) [ 9 , 10 , 11 , 12 , 13 , 14 ]. Heat waves and rising temperatures have also been linked to increased negative emotions and stress [ 14 , 15 , 16 ], hospitalizations for mood and behavioral disorders [ 17 ], mortality in patients with mental and behavioral health disorders [ 18 , 19 ], and increased rates of suicide [ 20 , 21 , 22 , 23 ] and homicide [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hanoi’s urban structure and boundary were expanded in 2008, and policies have strongly promoted population density and social development [ 12 ]. Moreover, in contrast to other urban areas in which studies of temperature and crime have been conducted, our data indicate that Hanoi has much lower crime rates than urban areas in other parts of the world, with an average crime count of 1.52 per day, compared to 39.7 in South Africa or 135 in Baltimore, Maryland [ 6 , 17 ], although this may be partially attributable to differences in policing and crime reporting.…”
Section: Discussioncontrasting
confidence: 81%
“…Little research has been conducted in developing countries to examine the effects of temperature on crime, and no study has been conducted in Vietnam. Gates et al found an increase in homicides for each 1 °C in maximum temperature in South Africa [ 6 ]. However, Trujillo et al indicated that each 1 °C in maximum temperature is associated with a 0.8% increase in interpersonal violence but decrease in homicides in Colombia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence links high temperatures with aggressive behavior, violent crime, and possibly suicide. 65 66 67 68 Such societal tension can escalate into armed conflict. In addition, several dry cities are in areas with already fragile states.…”
Section: Specific Health Considerationsmentioning
confidence: 99%